Penguatan Ekonomi Lokal Lipeksi melalui Literasi Keuangan Syariah dan Digitalisasi Produk Unggulan UMKM - Kholid Albar; Lidia Aditama Putri; Adi Basuki Choirul; Dyah Ayu Firnanda; Zunita Zunita; Moh. Rizqi Alifiransyah (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
MSME empowerment based on Islamic financial literacy and the digitalization of featured products is an important strategy for strengthening an inclusive and sustainable local economy. This community service program aimed to improve the capacity of Lipeksi MSME actors to understand Islamic financial principles, manage business finances transparently, and utilize digital technology for product marketing. The program was implemented through needs analysis, training and workshops, group discussions, mentoring, and assistance. The materials covered Islamic financial principles, capital management, simple financial recording, the use of digital financial applications, online marketing, and the strengthening of featured products. The results show that participants improved their understanding of Islamic financial literacy, particularly in transaction transparency, separation of personal and business finances, and awareness of Islamic financing alternatives. Participants also demonstrated greater readiness to use digital media, financial applications, and online platforms as tools for business promotion and management. Group discussions strengthened networking among MSMEs, while mentoring helped participants apply the training materials to their daily business practices. The discussion indicates that integrating Islamic financial literacy, digitalization, product innovation, and community collaboration can serve as a relevant empowerment model for local MSMEs. This program implies the need for continuous assistance that measures changes in financial behavior, technology adoption, access to Islamic financing, and the strengthening of business networks.